Combine harvesting introduced in Southeast Asia - CGIAR Research Program on Rice (2019)
Combine harvesting has replaced mechanised harvesting in the Mekong Delta, all major rice growing provinces in Cambodia, in Thailand and increasingly also in the Philippines, Myanmar and Indonesia. This was supported by IRRI through field demonstrations in Cambodia, market studies, round tables, training and accompanying studies involving life cycle assessment and business models for contract service provision.